Snap-valve cerebral shunt design for intracranial pressure operation and ultrasound visualization. (April 2019) - Mitchell, S.C.; Grangard, G.; Kahouli, W.; Dalldorf, C.; Crain, A.; Lee, E.; Hamlin, A.; Feeney, L.; Johnstone, H.; Luke, G.P.; Diamond, S.G.; Bauer, D.F.
Highlights: Snap-though buckling (STB) shells can be converted to valves. STB valves can function in the physiologic range for intracranial pressure. STB valves have a small form factor, and robust cycle reliability. STB valves can be made from antibiotic impregnated materials. STB valves can be easily and reliably monitored with clinical ultrasound. Abstract: Cerebral spinal fluid (CSF) shunts are the main treatment for hydrocephalus. They divert excess CSF from the ventricular system to the abdominal, pleural, or intravascular space where it is absorbed. The shunt valve regulates flow based on intracranial pressure (ICP) to maintain a physiologically stable and safe ICP. Shunt malfunction is difficult to detect, life-threatening and common. The present study demonstrates that snap-though buckling (STB) shells can be transformed into pressure-relief valves that act in the normal physiological range of ICP. Three different shell designs in this preliminary experiment were found to have opening and closing pressures that fall within the physiologically normal range of ICP of 6 to 25 cm H2 O. Furthermore, these STB shells demonstrate a valve actuation that is visible by ultrasound and have an implantable form-factor that is similar to currently available shunt valves. The unique characteristics of STB shell valves have potential clinical applications for shunt monitoring using ultrasound imaging and can be fabricated from antibiotic-impregnated materials to mitigate shunt infection. These characteristics make STB valves attractive for future use in cerebral shunt systems.